(untitled) (CIPEEX, 2024)
HAP (HEALTH AND PSYCHOLOGY) IS AN INNOVATIVE PLATFORM THAT AIMS TO FACILITATE ACCESS TO MENTAL HEALTH CARE. DEVELOPED USING A METHODOLOGY FOCUSED ON USABILITY AND COLLABORATION WITH EXPERTS IN THE FIELD, THE PLATFORM OFFERS A WIDE RANGE OF SERVICES, FROM ONLINE AND FACE-TO-FACE CONSULTATIONS TO ISSUING PRESCRIPTIONS AND ACCESS TO A BANK OF MEDICINES. THIS MAKES CARE MORE CONVENIENT AND ACCESSIBLE FOR PATIENTS AND MENTAL HEALTH PROFESSIONALS. THE DEVELOPMENT OF HAP INCLUDES THE CREATION OF THE WEB AND MOBILE PLATFORM, ALLOWING PATIENTS TO ACCESS MENTAL HEALTH SERVICES FROM ANYWHERE. A NETWORK OF QUALIFIED PROFESSIONALS, INCLUDING PSYCHOLOGISTS, PSYCHIATRISTS, THERAPISTS AND OTHER SPECIALISTS, IS AVAILABLE TO MEET PATIENTS’ SPECIFIC NEEDS. IN ADDITION, THE PLATFORM OFFERS INFORMATIVE CONTENT IN VIDEO FORMAT, ENRICHING THE EXPERIENCE FOR ALL USERS. THE RESULTS EXPECTED FROM HAP ARE IMPRESSIVE. THE PLATFORM HAS THE POTENTIAL TO SIGNIFICANTLY IMPROVE ACCESS TO MENTAL HEALTH CARE, MAKING IT MORE ACCESSIBLE REGARDLESS OF GEOGRAPHICAL LOCATION. THE POSSIBILITY OF ONLINE CONSULTATIONS CONTRIBUTES TO REDUCING COSTS, MAKING TREATMENT MORE ACCESSIBLE. THIS CAN INCREASE COMPETITION IN THE MENTAL HEALTH SERVICES MARKET AND LEAD TO AN OVERALL REDUCTION IN PRICES, MAKING TREATMENT ACCESSIBLE TO ALL. THE IMPACTS OF HAP ARE WIDE-RANGING AND INCLUDE IMPROVING PEOPLE’S MENTAL WELL-BEING, REDUCING THE STIGMA ASSOCIATED WITH THERAPY AND MEDICATION, THE CONVENIENCE OF SCHEDULING APPOINTMENTS AND OBTAINING PRESCRIPTIONS THROUGH THE PLATFORM, AND SUPPORTING MENTAL HEALTH PROFESSIONALS. IN ADDITION, THE PLATFORM CAN CREATE JOBS IN THE MENTAL HEALTH FIELD AND BOOST THE ECONOMY BY PROMOTING ACCESS TO NECESSARY TREATMENTS. HAP HAS THE POTENTIAL TO POSITIVELY TRANSFORM THE WAY PEOPLE ACCESS AND RECEIVE MENTAL HEALTH CARE. BY REMOVING OBSTACLES AND SIMPLIFYING THE PROCESS, THE PLATFORM CREATES AN ENVIRONMENT IN WHICH MENTAL HEALTH IS A PRIORITY ACCESSIBLE TO ALL, PROMOTING A POSITIVE IMPACT ON SOCIETY AS A WHOLE.